Porous ceramic modified water and fertilizer retention material as well as preparation method and application thereof

By using chitosan and cetyl trimethylammonium bromide as modifiers in porous ceramics, the water-retaining and fertilizer retention performance of porous ceramics is improved, the cost-effective and difficult degradation problems are solved, and the adsorption capacity and fertilizer release speed of ammonium nitrogen fertilizer are improved.

CN119591443APending Publication Date: 2025-03-11SANYA SCI & EDUCATION INNOVATION PARK WUHAN UNIV OF TECH

Patent Information

Application Number
CN202411736145.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Existing porous ceramics are not effective when used in the agricultural field to retain water and fertilizer, and plant water and fertilizer materials are costly and difficult to degrade.

Method used

By selecting the modifier chitosan and/or cetyl trimethylammonium bromide, the components of porous ceramics are prepared to improve their water and fertilizer retention properties.

Benefits of technology

It improves the water-retaining and fertilizer-retaining performance of porous ceramics, reduces production costs, solves the problem of high cost and difficulty in degrading plant water-retaining and fertilizer-retaining materials, and increases the static adsorption capacity of ammonium nitrogen fertilizer by 60%, and can slow down the release rate of adsorbed fertilizer within 24 hours.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591443A_ABST
    Figure CN119591443A_ABST
Patent Text Reader

Abstract

The invention discloses a porous ceramic modified water and fertilizer retention material as well as a preparation method and application thereof. The porous ceramic modified water and fertilizer retention material comprises porous ceramic balls and an organic modifier compounded with the porous ceramic balls, the organic modifier comprises one or more of chitosan and hexadecyl trimethyl ammonium bromide; the modified porous ceramic is obtained by selecting the modifier chitosan and / or hexadecyl trimethyl ammonium bromide and blending the components of the porous ceramic, the water and fertilizer retention performance of the porous ceramic is improved, the production cost is reduced, the problems of high cost and difficult degradation of a plant water and fertilizer retention material are solved, the static adsorption capacity on an ammonium nitrogen fertilizer is improved by 60%, and the application prospect is wide. The release speed of the adsorbed fertilizer within 24 hours can be slowed down, and the environment-friendly significance is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of plant water- and fertilizer-retaining materials, and in particular to a water- and fertilizer-retaining material modified with porous ceramics, and a preparation method and application thereof. Background Art

[0002] Water and nutrients (fertilizer) are fundamental conditions for crop growth. Water- and fertilizer-retaining materials can address issues such as water scarcity and low fertilizer absorption rates, thereby increasing crop yields. However, the materials available for water- and fertilizer-retaining are limited.

[0003] Porous ceramics have a series of advantages such as excellent specific surface area, low volume density, high thermal insulation efficiency, high porosity and rich surface properties, and are widely used in many scientific fields such as energy conservation and environmental protection, chemical smelting, biopharmaceuticals, etc. Porous ceramics are directly used in the agricultural field, but the effect of water and fertilizer retention is not good. Therefore, there is an urgent need for a method based on porous ceramic modification to improve the water and fertilizer retention capacity of plants. Summary of the Invention

[0004] In view of this, the present application provides a water-retaining and fertilizer-retaining material modified by porous ceramics, and a preparation method and application thereof, to solve the problem of how to improve the water-retaining and fertilizer-retaining effect of porous ceramics.

[0005] In order to achieve the above technical objectives, this application adopts the following technical solutions: In a first aspect, the present application provides a water-retaining and fertilizer-retaining material modified by porous ceramics, comprising porous ceramic balls and an organic modifier compounded with the porous ceramic balls; the organic modifier comprises one or more of chitosan and hexadecyltrimethylammonium bromide.

[0006] Preferably, the porous ceramic balls are obtained by sintering 80-90 parts of diatomaceous earth, 20-30 parts of shells and 30-40 parts of gluten powder, based on mass.

[0007] Preferably, the chemical composition of diatomaceous earth is as follows, calculated by mass: SiO2: 84.69-85 parts; CaO: 0.33-0.5 parts; Al2O3: 5.19-5.5 parts; Fe2O3: 1.83-2 parts; TiO2: 0.17-0.2 parts; MgO: 0.52-0.8 parts; K2O: 0.65-0.8 parts; Na2O: 0.32-0.5 parts; and the loss on ignition of diatomaceous earth is 6.30%-7%.

[0008] Preferably, the chemical composition of the shell is as follows, by mass: SiO2: 0.59-0.65 parts; CaO: 52.13-55 parts; Al2O3: 0.23-0.25 parts; Fe2O3: 0.07-0.1 parts; MgO: 0.44-0.5 parts; K2O: 0.03-0.05 parts; Na2O: 0.87-0.9 parts; the loss on ignition of the shell is 45.64%-48%.

[0009] Preferably, the particle size of the gluten is 100-200 mesh.

[0010] In a second aspect, the present application provides a method for preparing a water-retaining and fertilizer-retaining material modified by porous ceramics, comprising the following steps: adding washed and dried porous ceramic balls to an organic modifier solution, stirring the reaction, and then drying to obtain a water-retaining and fertilizer-retaining material modified by porous ceramics.

[0011] Preferably, the method comprises the following steps: washing the porous ceramic balls with deionized water and drying them to obtain pretreated porous ceramic balls; adding chitosan to an acetic acid solution and stirring at room temperature to obtain a chitosan acetic acid sol; adding the pretreated porous ceramic balls to the chitosan acetic acid sol, stirring for reaction, and then drying to obtain a water-retaining and fertilizer-retaining material modified with porous ceramics.

[0012] Preferably, the mass ratio of the porous ceramic balls to chitosan is 2:1-2.

[0013] Preferably, the method comprises the following steps: washing the porous ceramic balls with deionized water and drying them to obtain pretreated porous ceramic balls; adding the pretreated porous ceramic balls to an acid solution, heating and stirring, to obtain acidified porous ceramic balls; washing the acidified porous ceramic balls alternately with deionized water and anhydrous ethanol until neutral; adding the washed acidified porous ceramic balls to a hexadecyltrimethylammonium bromide solution, stirring for reaction, and then drying to obtain a water-retaining and fertilizer-retaining material modified with porous ceramics.

[0014] Preferably, the mass ratio of the porous ceramic balls to cetyltrimethylammonium bromide is 10:1-2.

[0015] The beneficial effects of the present application are as follows: The present application obtains modified porous ceramics by selecting the modifier chitosan and / or hexadecyltrimethylammonium bromide, and formulating the components of porous ceramics, thereby improving the water and fertilizer retention performance of the porous ceramics, reducing production costs, and solving the problems of high cost and difficulty in degradation of plant water and fertilizer retention materials. The static adsorption capacity of ammonium nitrogen fertilizer is increased by 60%, and the release rate of the adsorbed fertilizer within 24 hours can be slowed down, which is of environmental significance. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 SEM images of materials modified with different porous ceramics; Figure 2 FT-IR spectra of materials modified with different porous ceramics; Figure 3 The graph is a relationship between the adsorption amount of ammonium chloride and time of materials modified with different porous ceramics; Figure 4 The graph is a relationship between the release amount of ammonium chloride and time of materials modified with different porous ceramics; Figure 5 The graph shows the relationship between the leaching loss rate and the leaching times of materials modified with different porous ceramics. DETAILED DESCRIPTION

[0017] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0018] The present application provides a water-retaining and fertilizer-retaining material modified by porous ceramics, comprising porous ceramic balls and an organic modifier compounded with the porous ceramic balls; the organic modifier comprises one or more of chitosan and hexadecyltrimethylammonium bromide.

[0019] The present application obtains modified porous ceramics by selecting modifiers chitosan and / or hexadecyltrimethylammonium bromide, and formulating components of porous ceramics, thereby improving the water and fertilizer retention properties of the porous ceramics, reducing production costs, and solving the problems of high cost and difficulty in degradation of plant water and fertilizer retention materials. The static adsorption capacity of ammonium nitrogen fertilizer is increased by 60%, and the release rate of the adsorbed fertilizer within 24 hours can be slowed down, which is of environmental significance.

[0020] In some embodiments, the porous ceramic balls are obtained by sintering 80-90 parts of diatomaceous earth, 20-30 parts of shells and 30-40 parts of gluten powder, based on mass.

[0021] The raw materials of the porous ceramic balls of the present application are diatomaceous earth and shells, which are easy to obtain. The prepared porous ceramic microspheres have a high porosity, which is beneficial to improving the water retention effect.

[0022] In some embodiments, the chemical composition of diatomaceous earth is as follows, by mass: SiO2: 84.69-85 parts; CaO: 0.33-0.5 parts; Al2O3: 5.19-5.5 parts; Fe2O3: 1.83-2 parts; TiO2: 0.17-0.2 parts; MgO: 0.52-0.8 parts; K2O: 0.65-0.8 parts; Na2O: 0.32-0.5 parts; the loss on ignition of diatomaceous earth is 6.30%-7%.

[0023] Diatomaceous earth raw materials are easy to obtain, and when used in combination with shell raw materials, the cost of raw materials can be further controlled while ensuring product performance.

[0024] In some embodiments, the chemical composition of the shell is as follows, by mass: SiO2: 0.59-0.65 parts; CaO: 52.13-55 parts; Al2O3: 0.23-0.25 parts; Fe2O3: 0.07-0.1 parts; MgO: 0.44-0.5 parts; K2O: 0.03-0.05 parts; Na2O: 0.87-0.9 parts; the loss on ignition of the shell is 45.64%-48%.

[0025] Shells, as marine waste, are widely available and inexpensive. Using them extensively as raw materials not only reduces procurement costs but also effectively addresses the environmental pollution and resource waste caused by massive accumulation of shells.

[0026] In some embodiments, the gluten has a particle size of 100-200 mesh.

[0027] The gluten used in this application is used as a pore-forming agent to form abundant pores, so that the ceramic has a higher porosity. This porous structure is beneficial to the permeation, adsorption and storage of gases and liquids.

[0028] In a second aspect, the present application provides a method for preparing a water-retaining and fertilizer-retaining material modified by porous ceramics, comprising the following steps: adding washed and dried porous ceramic balls to an organic modifier solution, stirring the reaction, and then drying to obtain a water-retaining and fertilizer-retaining material modified by porous ceramics.

[0029] The present invention uses marine waste shells, natural mineral diatomaceous earth and modifiers as main raw materials to prepare modified porous ceramics, uses fertilizer to adjust water, uses water to promote fertilizer, gives full play to the synergistic effect between water and fertilizer, improves the utilization efficiency of water and fertilizer, improves soil ecology without increasing the usage amount, increases crop yields and boosts economic benefits.

[0030] In some embodiments, the method includes the following steps: washing the porous ceramic balls with deionized water and drying them to obtain pretreated porous ceramic balls; adding chitosan to an acetic acid solution and stirring at room temperature to obtain a chitosan acetic acid sol; adding the pretreated porous ceramic balls to the chitosan acetic acid sol, stirring the reaction, and then drying to obtain a water-retaining and fertilizer-retaining material modified with porous ceramics.

[0031] In some embodiments, the mass ratio of the porous ceramic balls to chitosan is 2:1-2.

[0032] In some embodiments, the method includes the following steps: washing the porous ceramic balls with deionized water and drying them to obtain pretreated porous ceramic balls; adding the pretreated porous ceramic balls to an acid solution, heating and stirring, to obtain acidified porous ceramic balls; washing the acidified porous ceramic balls alternately with deionized water and anhydrous ethanol until neutral; adding the washed acidified porous ceramic balls to a hexadecyltrimethylammonium bromide solution, stirring to react, and then drying to obtain a water-retaining and fertilizer-retaining material modified with porous ceramics.

[0033] In some embodiments, the mass ratio of the porous ceramic balls to cetyltrimethylammonium bromide is 10:1-2.

[0034] The present invention is further described below through specific examples.

[0035] Raw material preparation The preparation method of the porous ceramic balls used in the examples and comparative examples of this application is as follows: Porous ceramic balls were prepared by mixing 80 parts by mass of diatomaceous earth, 20 parts by mass of shells, and 30 parts by mass of 100-mesh wheat gluten and sintering at 1000°C for 5 hours. The chemical composition of the diatomaceous earth, by mass, is as follows: SiO₂: 84.69 parts; CaO: 0.33 parts; Al₂O₃: 5.19 parts; Fe₂O₃: 1.83 parts; TiO₂: 0.17 parts; MgO: 0.52 parts; K₂O: 0.65 parts; and Na₂O: 0.32 parts. The diatomaceous earth had a loss on ignition of 6.30%. The chemical composition of the shells is as follows by mass: SiO2: 0.59 parts; CaO: 52.13 parts; Al2O3: 0.23 parts; Fe2O3: 0.07 parts; MgO: 0.44 parts; K2O: 0.03 parts; Na2O: 0.87 parts; the loss on ignition of the shells is 45.64%.

[0036] Example 1 A method for preparing a water- and fertilizer-retaining material modified with porous ceramics comprises the following steps: Pretreatment: Weigh 10 g of the sintered porous ceramic balls, wash them several times with deionized water, and then dry them in an oven at 80 °C for 3 h before use. Preparation of sol: Weigh 5 g of chitosan and add it to 100 ml of 4% acetic acid solution, then stir continuously at room temperature until the chitosan is completely dissolved in the solution to obtain chitosan acetic acid sol; Mixing: The pretreated porous ceramic balls were added to the prepared chitosan acetate sol, and then magnetically stirred at 25 °C and 300 r / min for 12 h; Drying: The porous ceramic balls after magnetic stirring were taken out and dried in an oven at 60°C for 12 h to obtain chitosan-modified porous ceramic balls, which are water-retaining and fertilizer-retaining materials modified with porous ceramics.

[0037] Example 2 A method for preparing a water- and fertilizer-retaining material modified with porous ceramics comprises the following steps: Weigh 10 g of the sintered porous ceramic balls, wash them several times with deionized water, and then dry them in an oven at 80 °C for 3 h before use. Acidification: Add the rinsed porous ceramic balls to 400 ml of 10 mol / L HCl solution and stir at 300 r / min for 2 h in a magnetic stirrer maintained at 65 °C. Washing: The acidified porous ceramic balls were washed alternately with deionized water and anhydrous ethanol several times to make the pH value of the porous ceramic balls neutral; Mixing: Add the washed porous ceramic balls to 50 ml of 2% hexadecyltrimethylammonium bromide solution and stir at 180 r / min in a magnetic stirrer at room temperature for 2 h. Drying: The mixed porous ceramic balls were dried in an oven at 60°C for 3 h to obtain hexadecyltrimethylammonium bromide-modified diatomaceous earth porous ceramics, which are water- and fertilizer-retaining materials modified using porous ceramics.

[0038] Comparative Example 1 A method for preparing a porous ceramic modified material comprises the following steps: Pretreatment: Weigh 10 g of the sintered porous ceramic balls, wash them several times with deionized water, and then dry them in an oven at 80 °C for 3 h before use. Ultrasonication: Add the dried porous ceramic balls to 100 ml of 2 mol / L MgCl2·H2O solution and ultrasonicate for 30 min. Mixing: The ultrasonically treated solution and the porous ceramic balls were magnetically stirred at 300 r / min at 25 °C for 12 h, during which 100 ml of the prepared NaOH (5 mol / L) solution was slowly added dropwise. Standing: Let the stirred solution stand at room temperature for 24 h and filter; Washing: Wash the porous ceramic balls obtained by filtration with deionized water and anhydrous ethanol alternately for several times to remove the residual Cl in the ceramic balls. - ; Drying: The washed porous ceramic balls were dried in an oven at 80 °C for 3 h; Calcination: The dried porous ceramic balls were calcined at 450 °C for 2 h to obtain MgO-loaded diatomite porous ceramic balls, which are porous ceramic modified materials.

[0039] Testing and Evaluation The physical properties of the modified materials obtained in Examples 1-2 and Comparative Example 1 were tested using porous ceramic balls as blank controls. The results are shown in Table 1.

[0040] Based on Archimedes' principle, the water absorption (Wa), porosity (Pa), and bulk density (D) of samples fired at different temperatures were determined using the drainage method. The mass M1 (dry weight) of the dried sample was measured using a SHIMADZU-AUY120X hydrometer. The sample was immersed in a vacuum environment for 30 minutes using the TXY digital ceramic water absorption meter from Xiangtan Xiangyi Instrument Co., Ltd. to achieve water saturation. The saturated sample was then immersed in water, and the sample mass M2 (suspended weight) was measured using a hydrometer. The sample was removed from the immersion liquid, and the liquid droplets on the surface of the saturated sample were wiped off with a saturated towel. The sample mass M3 (wet weight) was then measured. The specific calculation formula is as follows:

[0041]

[0042]

[0043] Where: Wa is water absorption, %; Pa is porosity, %; D is bulk density, g / cm 3 ; D1 is the density of the immersion liquid, g / cm 3 In this study, the immersion liquid used in measuring water absorption was water, whose density was 1 g / cm 3 .

[0044] Table 1 Physical properties test results

[0045] Table 1 shows the physical properties of the water- and fertilizer-retaining materials modified with porous ceramics provided in Examples 1-3 of the present invention. As can be seen from Table 1, the water absorption, porosity, and compressive strength of the modified samples decreased to varying degrees compared to the blank control group. The water absorption of Comparative Example 1 of the present invention was severely reduced, by approximately 30% compared to the blank control group. The compressive strength of the sample in Example 2 of the present invention was the lowest, only half that of the blank control group. Therefore, Example 1 of the present invention had the best overall physical properties among the three groups of modified samples, with little change in porosity and compressive strength.

[0046] Figure 1The SEM images of the water-retaining and fertilizer-retaining materials modified with porous ceramics provided in Examples 1-2 and Comparative Example 1 of the present invention; Figure 1 It can be seen that the morphology of the diatomite porous ceramic sample modified with chitosan provided in Example 1 of the present invention did not change significantly compared with the blank control group sample, and there was no obvious chitosan loading feature. Considering the physical properties of the comprehensive sample and the infrared test results, after modification, chitosan formed a film on the surface of the sample instead of being loaded inside the porous ceramic. Therefore, the water absorption and porosity of the sample decreased slightly, but the compressive strength was the best among the three embodiments; a large number of whisker-like network structures appeared on the glass phase surface of the diatomite porous ceramic sample modified with magnesium chloride hexahydrate provided in Comparative Example 1 of the present invention, which may be because the ceramic matrix was formed during the preparation process. The glass phase in the body is corroded by a relatively high concentration of sodium hydroxide solution, and then new grains nucleate and grow during calcination, but the relatively low calcination temperature and short calcination time are not enough to make it fully formed, and finally form the morphology shown in the figure; the broken particles in the diatomaceous earth porous ceramic sample modified with hexadecyltrimethylammonium bromide provided in Example 2 of the present invention are reduced compared with those before modification, and the surface morphology of the diatomaceous earth is clearer, indicating that the microstructure of the porous ceramics formed by diatomaceous earth-shells with different modifiers is affected. The presence of broken particles will affect the gaps between the sample grains, and then affect the water absorption rate and porosity of the sample, which will reduce the water and fertilizer retention effect.

[0047] Figure 2 FT-IR spectra (infrared absorption spectra) of the water-retaining and fertilizer-retaining materials modified with porous ceramics provided in Examples 1-2 and Comparative Example 1 of the present invention. Figure 2 It can be seen that the modified porous ceramic sample provided in Example 1 has a -1 An absorption peak appears at 479 cm, which should be the characteristic absorption peak of the amide I band (C==O) of the amide group of chitosan; the sample modified with magnesium chloride hexahydrate provided in Comparative Example 1 has an absorption peak at 479 cm -1 The absorption peak at 2925cm-1 of the unmodified blank control group sample is wider and narrower, showing no obvious MgO-loaded characteristics. The inorganic modification method using magnesium chloride hexahydrate as a modifier has not met expectations. The D2 formula material did not load MgO as expected in the experimental design. Instead, it was corroded by a concentrated sodium hydroxide solution during the preparation process, and the surface morphology of the grains changed, causing a significant decrease in its water absorption rate and compressive strength. The adsorption capacity for ammonium nitrogen fertilizer was also close to that of the blank control group. The modified porous ceramic sample provided in Example 2 has a 2925cm-1 -1 and 2852 cm -1 Two new absorption peaks were added, which should be attributed to the symmetrical stretching vibration and bending vibration of CH. In addition, the samples of Example 1 and Example 2 showed a peak at 3436 cm -1The absorption peaks near become broader and stronger, which is the result of the combined effect of the stretching vibration peaks of NH and OH and the characteristic absorption peak of -NH2, indicating that chitosan and hexadecyltrimethylammonium bromide exist in the samples of Example 1 and Example 2 after modification.

[0048] Figure 3 The graph of the relationship between the adsorption amount of ammonium chloride and time of the water-retaining and fertilizer-retaining material samples modified with porous ceramics provided in Examples 1-2 and Comparative Example 1 of the present invention is shown. Figure 3 As can be seen, the adsorption curves of Comparative Example 1 of the present invention and the blank control group are basically consistent, indicating that the modification did not have a significant effect on fertilizer retention and improvement. The samples of Example 1 and Example 2 showed a significant increase in the adsorption capacity of ammonia nitrogen in ammonium chloride, with the maximum adsorption capacity over 24 hours reaching 0.119 mg / g and 0.145 mg / g, respectively. Compared with 0.090 mg / g of the unmodified porous ceramic balls, these increases were approximately 32.22% and 61.11%, respectively.

[0049] Figure 4 The graph of the relationship between the release amount of ammonium chloride and time of the water-retaining and fertilizer-retaining material samples modified with porous ceramics provided in Examples 1-3 of the present invention is shown. Figure 4 It can be seen that the rate of ammonium chloride release from saturated samples is D1>D2>D4>D3. The initial release rate of samples D2 and D4 is in the middle, but the maximum release amount in 24 hours is the lowest among the four groups of samples, which is 0.027 mg / g. This is because the adsorption capacity of samples D2 and D4 (blank control group) is weak. The power of static release mainly comes from the difference in ammonium chloride concentration between the sample and the solution, but the 24-hour adsorption amount of the two is small. The longer the release time, the smaller the concentration difference between the sample and the solution, and the lower the power of ammonium chloride diffusion. The 24-hour release amount of sample D3 is 0.033 mg / g. Due to the dissociated ion Br - Due to the presence of cetyltrimethylammonium bromide, an anion exchange membrane is easily formed on the outside of the sample, which has a good adsorption effect on cations. Therefore, the D3 sample performs well in both the static adsorption experiment and the static release experiment. The D1 sample has the fastest release rate and the maximum release amount in 24 hours is also the largest, which is 0.043 mg / g. This is because in an acidic environment, chitosan is more likely to be protonated and react with NH in water. 4+ Ion exchange occurs, and in the static release experiment, the experimental conditions are changed. The experimental solution is changed from ammonium chloride to deionized water, and the experimental environment is changed from weakly acidic to neutral, and the adsorption capacity of the sample decreases.

[0050] Figure 5 The relationship curve between the leaching loss rate and the leaching times of the water-retaining and fertilizer-retaining material samples modified with porous ceramics provided in Examples 1-3 of the present invention is shown. Figure 5It can be seen that after one leaching, the leaching loss is D4 > D3 > D1 > D2. However, as the number of leaching increases, the leaching loss gradually changes to D4 > D2 > D1 > D3. The leaching loss of the three modified samples after five leaching decreases by 19.55%, 18.24%, and 24.99%, respectively, compared to the blank control group D4. The slope of the D3 curve is significantly lower than that of the other curves. Although the initial leaching loss is large, the D3 sample modified with hexadecyltrimethylammonium bromide performs best over a long period of multiple leaching. The chitosan-modified porous ceramic balls also have a certain ability to increase water retention.

[0051] In summary, we can know that: The porous ceramic provided in Example 1 of the present invention has a water absorption rate of 81.04%, a porosity of 64.55%, a compressive strength of up to 2.46 MPa, and a bulk density of 0.80 g / cm 3 Chitosan modification has limited improvement on the performance of diatomite-shell porous ceramics. The comprehensive physical properties of the material modified with chitosan are the best in the formula, and the absorption capacity of ammonium nitrogen fertilizer is enhanced, with the adsorption amount increased by 32.22% relative to the blank group (no modifier). The main reason may be that during the modification process, chitosan is not loaded inside the matrix, but forms a film on the surface of the matrix. In an acidic environment, chitosan is protonated and reacts with NH4+ in the water. 4+ Ion exchange occurs to complete the NH 4+ adsorption.

[0052] The porous ceramic provided in Comparative Example 1 of the present invention has a water absorption rate of 69.56%, a porosity of 59.73%, a compressive strength of up to 1.76 MPa, and a bulk density of 0.86 g / cm 3 The inorganic modification method using magnesium chloride hexahydrate as a modifier did not meet expectations. The material did not load MgO as expected in the experimental design. Instead, it was corroded by the concentrated sodium hydroxide solution during the preparation process, changing the surface morphology of the grains. This significantly reduced their water absorption and compressive strength, and their adsorption capacity for ammonium nitrogen fertilizer was close to that of the blank control group (no modifier).

[0053] The porous ceramic provided in Example 2 of the present invention has a water absorption rate of 85.76%, a porosity of 64.13%, a compressive strength of up to 1.54 MPa, and a bulk density of 0.75 g / cm 3Cetyltrimethylammonium bromide significantly improves the fertilizer retention capacity of diatomite-shell porous ceramics. Compared to the blank control (no modifier) ​​formulation, the formulation with cetyltrimethylammonium bromide as the modifier exhibited a slight decrease in water absorption, but increased its static adsorption capacity for ammonium nitrogen fertilizer by 60%, and also slowed the release rate of the adsorbed fertilizer within 24 hours. Fitting results indicate that the adsorption kinetics of the material with cetyltrimethylammonium bromide as the modifier better conform to the pseudo-second-order kinetic model, and the adsorption isotherm model better fits the Langmuir adsorption isotherm equation.

[0054] In response to the problems of the existing technology, the present invention modifies porous ceramics with chitosan and cetyltrimethylammonium bromide to prepare water-retaining and fertilizer-retaining materials, which can effectively solve the problems of high cost and difficult degradation of plant water-retaining and fertilizer-retaining materials. The static adsorption capacity of ammonium nitrogen fertilizer is increased by 60%, and the release rate of the adsorbed fertilizer within 24 hours is slowed down, while also improving the water retention performance.

[0055] The above are only preferred specific embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes or replacements that can be easily thought of by any technician familiar with this technical field within the technical scope disclosed by the present invention should be covered by the scope of protection of the present invention.

Claims

1. A water-retaining and fertilizer-retaining material modified by porous ceramics, characterized in that: The invention comprises porous ceramic balls and an organic modifier compounded with the porous ceramic balls; the organic modifier comprises one or more of chitosan and hexadecyltrimethylammonium bromide.

2. The water-retaining and fertilizer-retaining material modified by porous ceramics according to claim 1, characterized in that: The porous ceramic ball is obtained by sintering 80-90 parts of diatomaceous earth, 20-30 parts of shells and 30-40 parts of gluten powder by mass.

3. The water-retaining and fertilizer-retaining material modified by porous ceramics according to claim 2, characterized in that: The chemical composition of the diatomaceous earth is as follows, by mass: SiO2: 84.69-85 parts; CaO: 0.33-0.5 parts; Al2O3: 5.19-5.5 parts; Fe2O3: 1.83-2 parts; TiO2: 0.17-0.2 parts; MgO: 0.52-0.8 parts; K2O: 0.65-0.8 parts; Na2O: 0.32-0.5 parts; the loss on ignition of the diatomaceous earth is 6.30%-7%.

4. The water-retaining and fertilizer-retaining material modified by porous ceramics according to claim 2, characterized in that: The chemical composition of the shell is as follows, by mass: SiO2: 0.59-0.65 parts; CaO: 52.13-55 parts; Al2O3: 0.23-0.25 parts; Fe2O3: 0.07-0.1 parts; MgO: 0.44-0.5 parts; K2O: 0.03-0.05 parts; Na2O: 0.87-0.9 parts; the loss on ignition of the shell is 45.64%-48%.

5. The water-retaining and fertilizer-retaining material modified by porous ceramics according to claim 2, characterized in that: The particle size of the gluten powder is 100-200 meshes.

6. A method for preparing a water- and fertilizer-retaining material modified by porous ceramics as claimed in any one of claims 1 to 5, characterized in that: The following steps are involved: The washed and dried porous ceramic balls are added into the organic modifier solution, stirred for reaction, and then dried to obtain the water-retaining and fertilizer-retaining material modified by the porous ceramics.

7. The method for preparing a water- and fertilizer-retaining material modified by porous ceramics according to claim 6, characterized in that: The following steps are involved: The porous ceramic balls are washed with deionized water and dried to obtain pretreated porous ceramic balls; Adding chitosan into acetic acid solution and stirring at room temperature to obtain chitosan acetic acid sol; The pretreated porous ceramic balls are added into chitosan acetic acid sol, stirred for reaction, and then dried to obtain the water- and fertilizer-retaining material modified with porous ceramics.

8. The method for preparing a water- and fertilizer-retaining material modified by porous ceramics according to claim 7, characterized in that: The mass ratio of the porous ceramic balls to chitosan is 2:1-2.

9. The method for preparing a water- and fertilizer-retaining material modified by porous ceramics according to claim 6, characterized in that: The following steps are involved: The porous ceramic balls are washed with deionized water and dried to obtain pretreated porous ceramic balls; Adding the pretreated porous ceramic balls into an acid solution, heating and stirring, to obtain acidified porous ceramic balls; The acidified porous ceramic balls were washed alternately with deionized water and anhydrous ethanol until they were neutral; The washed acidified porous ceramic balls are added into a cetyltrimethylammonium bromide solution, stirred for reaction, and then dried to obtain the water-retaining and fertilizer-retaining material modified by porous ceramics.

10. The method for preparing a water- and fertilizer-retaining material modified by porous ceramics according to claim 9, characterized in that: The mass ratio of the porous ceramic balls to hexadecyltrimethylammonium bromide is 10:1-2.

Citation Information

Patent Citations

  • Preparation method of composite adsorption material for nitrogen oxide waste gas treatment

    CN108031233A

  • Chitosan modified bioceramic material and preparation method thereof

    CN108358658A

  • Soil remediation fertilizer and preparation method thereof

    CN112919971A

  • Amine-containing organic matter adsorption material and preparation method thereof

    CN118616000A

  • Porous ceramic prepared from marine waste shells and preparation method of porous ceramic

    CN118908746A

Cited By

  • Nutritional moisturizing ceramsite as well as preparation method, application and application method thereof

    CN120081706A